Secondary metabolism in the lichen symbiosis. (2nd November 2017) - Calcott, Mark J.; Ackerley, David F.; Knight, Allison; Keyzers, Robert A.; Owen, Jeremy G.
Abstract : Lichens, which are defined by a symbiosis between a mycobiont (fungal partner) and a photobiont (photoautotrophic partner), are in fact complex assemblages of microorganisms that constitute a largely untapped source of bioactive secondary metabolites. Abstract : Lichens, which are defined by a core symbiosis between a mycobiont (fungal partner) and a photobiont (photoautotrophic partner), are in fact complex assemblages of microorganisms that constitute a largely untapped source of bioactive secondary metabolites. Historically, compounds isolated from lichens have predominantly been those produced by the dominant fungal partner, and these continue to be of great interest for their unique chemistry and biotechnological potential. In recent years it has become apparent that many photobionts and lichen-associated bacteria also produce a range of potentially valuable molecules. There is evidence to suggest that the unique nature of the symbiosis has played a substantial role in shaping many aspects of lichen chemistry, for example driving bacteria to produce metabolites that do not bring them direct benefit but are useful to the lichen as a whole. This is most evident in studies of cyanobacterial photobionts, which produce compounds that differ from free living cyanobacteria and are unique to symbiotic organisms. The roles that these and other lichen-derived molecules may play in communication and maintaining the symbiosis are poorly understood at present. Nonetheless, advances in genomics, mass spectrometry and other analytical technologies are continuing to illuminate the wealth of biological and chemical diversity present within the lichen holobiome. Implementation of novel biodiscovery strategies such as metagenomic screening, coupled with synthetic biology approaches to reconstitute, re-engineer and heterologously express lichen-derived biosynthetic gene clusters in a cultivable host, offer a promising means for tapping into this hitherto inaccessible wealth of natural products.